Educação de adultos em tempos de violação aos direitos humanos: das palavras freireanas grávidas de mundo para as palavras ocas de vida do MOBRAL - Barbosa, Maria das Graças da Cruz (2014)
This research proposes to analyze the primer “MOBRAL’s Alphabetization Script”, from 1978, confronting with the freirean educational alphabetization purpose. “Conceiving de education as human right refers to consider the human being in his ontology vocation of wanting to be more” (SACAVINO, 2007, p. 458). So, we locked for the freirean pedagogy, the human rights, the Brazilian historic context, in the 1960 begnning, until the military dictatorship (1964-1985), the evidences of the education violation, as human right, in the script and in the documental and bibliographical MOBRAL’s studies. Therefore, the evidence method is our way. In this manner, we did a comparative study between freirean alphabetization purpose and the “MOBRAL’s Functional Education Program”, that we reported to the “Alphabetization Script Primer”, the “MOBRAL’s Base Document”, the Freire (1967;1979), Germano (1994), Jannuzzi (1979), Saviani (2008), Cunha; Góes (1985) studies and others. In the “MOBRAL’s Alphabetization Script Primer”, 1978, track was found an experience vestige of education to never more. The research showed that the MOBRAL’s alphabetization words were not the world full words, as in the freirean perspective, but in social mean empty words, life empty words, that considered the popular knowledge, the exclusion situation and the reality transformation capacity, using the world reading in articulation to the word reading.